Pembaruan Teknologi Informasi Pendidikan di Kotawaringin Timur Untuk Penilaian Dalam Pembelajaran K13 Berbasis Web - Imam Hanafi Rahman; Nurahman Nurahman (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Primary schools are schools of all schools that have implemented k13. Each school is located in East Kotawaringin, Central Kalimantan Province, Indonesia. The problems faced at this time are in the application of K13 which still uses Microsoft Word and Microsoft Excel and the management of transactions and reports as well as report cards still use manual and even traditional recording which results in frequent loss of data. So, how to make an information system that can make it easier for customers to place orders via the Website without coming directly to the market and manage transaction data and reports in a systemized manner. To solve this problem, we need a Web-based information system. To create this web-based information system, we need an editor software for Macromedia Dreamweaver CS4 programming language, PHP programming language, and MySQL database